Actinobacteria Community and Their Antibacterial and Cytotoxic Activity on the Weizhou and Xieyang Volcanic Islands in the Beibu Gulf of China - Wang, Lin; Peng, Chunyan; Gong, Bin; Yang, Zicong; Song, Jingjing; Li, Lu; Xu, Lili; Yue, Tao; Wang, Xiaolin; Yang, Mengping; Xu, Huimin; Liu, Xiong (Frontiers in Microbiology, 2022)
Weizhou Island and Xieyang Island are two large and young volcanic sea islands in the northern part of the South China Sea. In this study, high-throughput sequencing (HTS) of 16S rRNA genes was used to explore the diversity of Actinobacteria in the Weizhou and Xieyang Islands. Moreover, a traditional culture-dependent method was utilized to isolate Actinobacteria, and their antibacterial and cytotoxic activities were detected. Alpha diversity indices (ACE metric) of the overall bacterial communities for the larger island (Weizhou) were higher than those for the smaller island (Xieyang). Beta-diversity analysis showed a more dispersive pattern of overall bacterial and Actinobacteria communities on a larger island (Weizhou). At the order level, Frankiales, Propionibacteriales, Streptomycetales, Micrococcales, Pseudonocardiales, Micromonosporales, Glycomycetales, Corynebacteriales, and Streptosporangiales were the predominant Actinobacteria. 22.7% of the OTUs shared 88%-95% similarity with some known group. More interestingly, 15 OTUs formed a distinct and most predominant clade, and shared identities of less than 95% with any known families. This is the first report about this unknown group and their 16S rRNA sequences obtained from volcanic soils. A total of 268 actinobacterial strains were isolated by the culture-dependent method. Among them, 55 Streptomyces species were isolated, representing 76.6% of the total. S. variabilis and S. flavogriseus were the most abundant. Moreover, some rare Actinomycetes were isolated. These included Micromonospora spp., Nocardia spp., Amycolatopsis spp., Tsukamurella spp., Mycobacterium spp., Nonomuraea spp.. Among them, 10 Streptomyces spp. exhibited antibacterial activity against B. cereus. Only three strains inhibited the growth of E. coli. Six strains showed good activity against aquatic pathogenic bacterial strains of S. iniae. The cytotoxicity assay results showed that 27 strains (10.07%) exhibited cytotoxic activity against HeLa and A549 cell lines. Many Actinobacteria strains with cytotoxic activity were identified as rare Actinobacteria, which illustrated that volcanic islands are vast reservoirs for Actinobacteria with promising antibacterial and cytotoxic activity. This study may significantly improve our understanding of Actinobacteria communities on volcanic islands. The isolated Actinobacteria showed promising prospects for its utilization in the future.